2020
DOI: 10.1136/gpsych-2019-100180
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional study of internalised stigma and medication adherence in patients with obsessive compulsive disorder

Abstract: BackgroundPatients suffering from psychiatric disorders tend to stigmatise themselves which had been linked to poor adherence to treatment.AimsThe aim of the present study was to study internalised stigma and medication adherence and to assess the relationship between them in patients with obsessive compulsive disorder (OCD).MethodsA cross-sectional study was conducted on 112 patients diagnosed with OCD who were attending the Out-patient's department at Department of Psychiatry of a tertiary care hospital in N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 30 publications
(55 reference statements)
0
17
0
Order By: Relevance
“…Obsessive-compulsive disorder (OCD) is reported to be the fourth most frequent mental disorder worldwide [ 5 , 6 ]. OCD prevalence varies over age, regions, and others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obsessive-compulsive disorder (OCD) is reported to be the fourth most frequent mental disorder worldwide [ 5 , 6 ]. OCD prevalence varies over age, regions, and others.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, OCD can adversely affect academic performance, general well-being, social interaction, and suicidal thoughts. Issues that might have a huge impact on life unless being diagnosed early and properly managed [ 4 , 6 , 11 , 12 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Shapiro–Wilk test assessed the normality of the data. Sample size estimation concerning the first set of hypotheses was based on data from the studies of Ansari et al ( N = 112, r = 0.61 for the connection between the self-stigma and obsessive-compulsive symptoms), 20 Ociskova et al ( N = 109, r = 0.31 for the self-stigma and overall severity of the mental disorder, r = 0.33 for the self-stigma and anxiety, r = 0.55 for the self-stigma and depressive symptoms, and r = 0.44 for the self-stigma and dissociation), 22 and Grambal et al ( N = 184, Cohen’s d = 0.52 for the self-stigma in patients with and without a personality disorder) 21 with Prasko et al ( N = 63, Cohen’s d = 0.60 for the same purpose). 19 The estimation of the second set of hypotheses was based on data from the studies of Prasko et al ( N = 63, r = 0.50 for the self-stigma and the relative change of overall severity of the mental disorder and r = 0.27 for the relative change of the depressive symptoms) 19 and Ociskova et al ( N = 109, r = 0.26 the self-stigma and the relative change of anxiety).…”
Section: Methodsmentioning
confidence: 99%
“… 17 , 18 The self-stigma has been related to more severe symptoms of anxiety, depression, and dissociation in patients with depressive and anxiety disorders 19 and more severe OCD symptoms. 20 Patients with a personality disorder 21 , 22 show higher tendencies towards self-stigmatization, though not all studies find such connection. 23 In a study by Deres et al 24 inpatients with higher self-stigma showed lower engagement and working alliance in psychotherapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation